iENA 2013 - Universiti Malaysia Sarawak, ISITI-CoERI (Universiti Malaysia Sarawak (UNIMAS), 2013)
Award certificate for Prof. Dr. Alvin Yeo Wee for outstanding performances in International Trade Fair.